Maternal and childhood exposure to inorganic arsenic and airway allergy – A 15-Year birth cohort follow-up study. (January 2021) - Tsai, Tsung-Lin; Lei, Wei-Te; Kuo, Chin-Chi; Sun, Hai-Lun; Su, Pen-Hua; Wang, Shu-Li
Highlights: This is a 15-year follow-up study of birth cohort established in 2000-01 in Taiwan. Prenatal arsenic exposure was found to increase the risk of asthma in children. Postnatal arsenic exposure increased the risk of childhood allergic rhinitis. Abstract: Background: The prevalence of allergic diseases in children has increased globally. Early-life exposure to inorganic arsenic has been found to be associated with impaired immune function and decreased lung function in children; however, the results are inconsistent. We aimed to evaluate the effect of prenatal and childhood exposure to inorganic arsenic on allergic diseases in children, through a 15-year follow-up birth cohort study, conducted in central Taiwan. Methods: Children born to women enrolled in the Taiwan Maternal and Infant Cohort Study (TMICS-pilot) from December 2000 to November 2001 were recruited and followed every 2–3 years until the age of 14 years. Urinary specimens were collected in the pregnant women during the 3rd trimester and the followed children. Diagnoses of allergic diseases were based on physician diagnoses using the International Study of Asthma and Allergies in Childhood questionnaire. Urinary arsenic speciation was performed using high-performance liquid chromatography and inductively coupled plasma dynamic reaction cell mass spectrophotometry. Results: Of the 261 children from 358 mother-infant pairs for this study, those with asthma and allergic rhinitis reported a higher prevalence of maternal allergy (49.47%) than did non-allergic children (29.81%). In the fully adjusted model, levels of maternal urine (iAs + MMA + DMA) greater than the median were found to be significantly associated with an increased risk of asthma (OR = 4.28; 95% CI 1.32, 13.85). Levels of urinary (iAs + MMA + DMA) in children higher than the median were associated with an increased risk of allergic rhinitis (OR = 2.26; 95% CI 1.20, 4.26). Conclusion: Prenatal and childhood exposure to inorganic arsenic were found to be significantly associated with the occurrence of asthma and allergic rhinitis in children, respectively. Further large cohort follow-up studies are important to validate the association between inorganic arsenic exposure and allergic diseases in children.